The Battle of Ncome project: state memorialism, discomforting spaces - Dlamini, N. (Southern African Humanities, 2021)
This paper examines the Battle of Ncome project from the perspective of state memorialism in postapartheid South Africa. Documents on the project suggest that it was intended to achieve three main objectives: a 'correction' of the past, political reconciliation, and economic and cultural development. However, there is evidence which indicates that the project was to a greater extent a kind of ethnicised memorialism. Here I argue that the intended or unintended ethnicisation of the project provides discomforting spaces which are sources of concern, especially in the post-apartheid context where unity is the buzzword. I argue that the revival of the monument involved the erasure of key historical actors from the memory of this historical event. I point out that some academic historians who were part of state memorialism were also part of this reordering of Ncome memory in favour of Zulu ethnic nationalism. To cite this paper: Dlamini, N. 2001. The Battle of Ncome project: state memorialism, discomforting spaces. Southern African Humanities 13: 125-138.